Dampak pemudaran fungsi surau di Minangkabau: Analisis historis dan sosiologis - Husna, Lativa (Maliki Interdisciplinary Journal, 2024)
The fading function of Surau in Minangkabau has significantly impacted various aspects of life, including spiritual, social, and cultural dimensions. As an educational institution and religious center, Surau plays an active role in shaping community character and Minangkabau cultural identity. This research aims to analyze the development of Surau in Minangkabau, the factors leading to its fading function, and the impact of this change from a historical and sociological perspective. The research employed a qualitative method with a historical and sociological approach, conducting an in-depth analysis of Surau’s functions over time. The findings reveal that Surau once served as a center for religious education, a place of residence, a venue for deliberation, and a container for cultural preservation. However, over time, Surau’s role has gradually diminished due to modernization, urbanization, and changing lifestyles. These factors have led to a decline in the interest of younger generations in Surau activities and have threatened its existence. The research concludes that comprehensive strategies and collaboration among the community, government, and religious leaders are necessary to revitalize Surau’s function. These efforts are expected to restore Surau as a crucial pillar in the social, cultural, and religious life of Minangkabau society. Financial and moral support from all stakeholders is crucial to achieve this goal.